Cho m,n ∈N, p là số nguyên tố thỏa mãn `p/(m-1)=(m+n)/p`. CMR: `p^2=n+2` 28/09/2021 Bởi Gianna Cho m,n ∈N, p là số nguyên tố thỏa mãn `p/(m-1)=(m+n)/p`. CMR: `p^2=n+2`
Giải thích các bước giải: Ta có: `p/(m-1)=(m+n)/p=>p^2=(m-1)(m+n)` Mà `m,n∈N=>m-1;m+n∈N` `=>m-1,m+n∈`$Ư_{(p^2)}$ Mà `p` là số nguyên tố `=>`$Ư_{(p^2)}=$ `{1;p;p^2}` Lại có `n∈N` `=>n> -1` `=>m+n>m-1` $$⇒\left \{ {{m+n=p^2} \atop {m-1=1}} \right.⇒\left \{ {{p^2=n+m} \atop {m=2}} \right.⇒p^2=n+2$$ Vậy `p^2=n+2`. Bình luận
Giải thích các bước giải:
Ta có:
`p/(m-1)=(m+n)/p=>p^2=(m-1)(m+n)`
Mà `m,n∈N=>m-1;m+n∈N`
`=>m-1,m+n∈`$Ư_{(p^2)}$
Mà `p` là số nguyên tố `=>`$Ư_{(p^2)}=$ `{1;p;p^2}`
Lại có `n∈N`
`=>n> -1`
`=>m+n>m-1`
$$⇒\left \{ {{m+n=p^2} \atop {m-1=1}} \right.⇒\left \{ {{p^2=n+m} \atop {m=2}} \right.⇒p^2=n+2$$
Vậy `p^2=n+2`.